p(x) = x4 – 5x + 6, g(x) = 2 - x2
Answers
Answered by
2
Answer:
Quotient= and Remainder=
Step-by-step explanation:
Given : and
To divide the p(x) by g(x)
We know, Dividend = Divisor × quotient + remainder
p(x)= Dividend , g(x)=Divisor
= quotient + remainder
Solve by long division we get,
By dividing we get,
Quotient= and Remainder=
Step-by-step explanation:
Answered by
5
Step-by-step explanation:
p(x) = x4 – 5x + 6, g(x) = 2 – x2. Hence, here quotient is - (x2 + 2) and remainder is – 5x + 10.
Attachments:
![](https://hi-static.z-dn.net/files/d9a/3e8907665b0bdaf287164bdcf096ab58.jpg)
Similar questions